Bonding Effectiveness of Universal Adhesive to Intracoronal Bleached Dentin Treated with Sodium Ascorbate - Trindade,Thaís Fantinato (2016)
Abstract This study evaluated the effect of restorative protocol with sodium ascorbate on the shear bond strength (SBS) of a universal adhesive to intracoronal bleached dentin. One hundred-and-twenty bovine dentin fragments were randomly divided into 12 groups (n=10), according to the bleaching procedure (unbleached and bleached) and restorative protocol (no treatment, 10% sodium ascorbate -10SA, 35% sodium ascorbate -35SA and two-step etch-and-rinse -ER or one-step self-etch -SE Scotchbond universal adhesive approaches). Four whitening sessions were performed using 35% hydrogen peroxide. The samples from control groups were kept in relative humidity at 37 °C. Immediately after bleaching procedures, the assigned antioxidant solution was applied on dentin and restorative procedures were performed following either the ER or the SE approach. After 24 h, the specimens were subjected to SBS test. Data (MPa) were analyzed by ANOVA and Tukey's test (?=0.05). Lower SBS values were found for bleached specimens (8.54 MPa) compared with those unbleached (12.13 MPa) (p<0.05). The bond strength of the sodium ascorbate-treated groups was higher than those untreated, regardless of the strategy employed (p<0.05). Groups restored without sodium ascorbate showed lower bond strength values for both ER (8.32 MPa) and SE (8.28 MPa) adhesive strategies. The group treated with 10SA submitted to ER approach (10.14 MPa) was similar to untreated groups (p>0.05). It may be concluded that bond strength of composite resin to intracoronal dentin was affected by restorative protocol and reduced by bleaching.